2014
DOI: 10.1055/s-0033-1341080
|View full text |Cite
|
Sign up to set email alerts
|

Direct Guanylation of Amino Groups by Cyanamide in Water: Catalytic Generation and Activation of Unsubstituted Carbodiimide by Scandium(III) Triflate

Abstract: Guanylation proceeded efficiently upon treatment of the various amines with cyanamide in the presence of catalytic amounts of scandium(III) triflate under mild conditions. The method did not require the guanylation reagents to be preactivated, and the reaction proceeded efficiently in water. The method, therefore, has practical utility for substrates that dissolve only in aqueous solutions, for example, peptides or pharmacologically important compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 7 publications
(11 reference statements)
0
12
0
4
Order By: Relevance
“…More recently, Tsubokura et al reported a new protocol requiring milder reaction conditions. This reaction strategy involved the use of scandium(ӀӀӀ) triflate as Lewis acid catalyst (Tsubokura et al, 2014). On the other side, carbodiimides have attracted increasing attention for preparing complexes with a substituted propiolamidine group or a substituted guanidinate groups (Cao et al, 2011).…”
Section: Synthesis Of the Chitosan Derivativesmentioning
confidence: 99%
“…More recently, Tsubokura et al reported a new protocol requiring milder reaction conditions. This reaction strategy involved the use of scandium(ӀӀӀ) triflate as Lewis acid catalyst (Tsubokura et al, 2014). On the other side, carbodiimides have attracted increasing attention for preparing complexes with a substituted propiolamidine group or a substituted guanidinate groups (Cao et al, 2011).…”
Section: Synthesis Of the Chitosan Derivativesmentioning
confidence: 99%
“…Many therapeutic agents have been constructed from this scaffold such as Cimetidine 1 (treatment of heartburn and peptic ulcers) and Pinacidil 2 (treatment of hypertension) (Scheme ). Typical synthesis of guanidine involves reaction between an amine and guanylating agents such as isothioureas, carbodiimide, amidine, cyanamide, pyrrazole, triflylguanidines and thiourea . Among them, thiourea are the most promising guanylating agent because of their stability and ease of preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Literatūrā ir atrodamas anilīna tiešas pārvērtības par arilguanidīnu. [23][24][25][26][27][28] No tām izvēlējāmies guanilēšanu ar NH2CN, lai izstrādātu protokolu ar labāko atomu ekonomiju un zemākām izmaksām. 23,24 Ņemot vērā sākotnējā skrīninga rezultātus, tika pieņemts, ka trīs mainīgajiem apstākļiem (t. i., koncentrācijai, reakcijas laikam un NH2CN ekvivalentiem) varētu būt vislielākā ietekme uz reakcijas iznākumu.…”
Section: Starpprodukta 21 Guanilēšanaunclassified
“…[23][24][25][26][27][28] No tām izvēlējāmies guanilēšanu ar NH2CN, lai izstrādātu protokolu ar labāko atomu ekonomiju un zemākām izmaksām. 23,24 Ņemot vērā sākotnējā skrīninga rezultātus, tika pieņemts, ka trīs mainīgajiem apstākļiem (t. i., koncentrācijai, reakcijas laikam un NH2CN ekvivalentiem) varētu būt vislielākā ietekme uz reakcijas iznākumu. Izvēlējāmies eksperimenta plānošanas pieeju (Design of Experiment, DoE), lai vienlaikus izpētītu visus trīs mainīgos lielumus un rezultātā noteiktu jebkādu mijiedarbību starp tiem.…”
Section: Starpprodukta 21 Guanilēšanaunclassified
See 1 more Smart Citation